2023
DOI: 10.3390/jcm12041356
|View full text |Cite
|
Sign up to set email alerts
|

The Sodium-Glucose Co-Transporter 2 (SGLT2) Inhibitor Empagliflozin Reverses Hyperglycemia-Induced Monocyte and Endothelial Dysfunction Primarily through Glucose Transport-Independent but Redox-Dependent Mechanisms

Abstract: Purpose: Hyperglycaemia-induced oxidative stress and inflammation contribute to vascular cell dysfunction and subsequent cardiovascular events in T2DM. Selective sodium-glucose co-transporter-2 (SGLT-2) inhibitor empagliflozin significantly improves cardiovascular mortality in T2DM patients (EMPA-REG trial). Since SGLT-2 is known to be expressed on cells other than the kidney cells, we investigated the potential ability of empagliflozin to regulate glucose transport and alleviate hyperglycaemia-induced dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Finally, we also observed a reduction in renal inflammation with Dapa, as indicated by reduced myeloid infiltration, which was consistent with the reduction in mitochondrial NLRP ( 57 ). Although SGLT2 expression in leukocytes in vivo is unclear, there are studies suggesting a direct effect of flozins on monocytes and endothelial cells in models of ischemic myocardial injury and in hyperglycemic or septic in vitro assays ( 58 60 ). Interestingly, Dapa reduced TLR4 and NF-κB activation in differentiated macrophages and human endothelial cells stimulated with LPS ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we also observed a reduction in renal inflammation with Dapa, as indicated by reduced myeloid infiltration, which was consistent with the reduction in mitochondrial NLRP ( 57 ). Although SGLT2 expression in leukocytes in vivo is unclear, there are studies suggesting a direct effect of flozins on monocytes and endothelial cells in models of ischemic myocardial injury and in hyperglycemic or septic in vitro assays ( 58 60 ). Interestingly, Dapa reduced TLR4 and NF-κB activation in differentiated macrophages and human endothelial cells stimulated with LPS ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this drug also suppressed M1 and promoted M2 macrophage polarization in postischemic hearts, suggesting a downregulation of inflammation ( 59 ). Moreover, incubation with empagliflozin reduced oxidative stress in human monocytes and endothelial cells exposed to hyperglycemic conditions, resulting in reduced chemotaxis and endothelial dysfunction ( 60 ). Although the reduced leukocyte infiltration observed in the IR + Dapa group may be an indirect effect of improved tubular repair, we cannot exclude a direct regulation of proinflammatory signals in immune and endothelial cells leading to an earlier resolution of inflammation with Dapa.…”
Section: Discussionmentioning
confidence: 99%
“…Semo et al revealed that empagliflozin reversed hyperglycemia-induced monocyte and endothelial dysfunction despite the fact that SGLT2 is not the primary glucose transporter in these cells. Its antioxidant effect was similar to N-acetyl-L-cysteine [ 186 ]. One of the last experiments showed that empagliflozin suppressed mitochondrial reactive oxygen species generation and mitigated the inducibility of atrial fibrillation in diabetic rats [ 182 ].…”
Section: Sodium-glucose Cotransporter-2 (Sglt2) Inhibitorsmentioning
confidence: 99%
“…Empagliflozin has also reported the decrease of superoxide and hydrogen peroxide induced by hyperglycemia in cultures of human proximal tubular epithelial cells, and in turn prevents the activation of inflammatory signaling pathways [ 304 ]. On the other hand, recent studies reported that empagliflozin would have antioxidant and anti-renal senescence effects mediated by SIRT1 in a d-galactose-induced aging model in rats [ 305 ] and also managed to restore endothelial dysfunction induced by hyperglycemia through the modulation of oxidative stress in human cell cultures [ 306 ].…”
Section: Effect Of Aging Diseases and Their Treatment On The Redox Ba...mentioning
confidence: 99%